Seismic Expression of Tectonic Features in the Lesser Sunda Islands, Indonesia - Darman, Herman (Berita Sedimentologi, 2012)
The Sunda Arc is a chain of islands in the southern part of Indonesia, cored by active volcanoes. The western part of the Sunda arc is dominated by the large of Sumatra and Java, and is commonly called "the Greater Sunda Islands‟. The tectonic terrain within this part is dominated by the oceanic subduction below the southeastern extension of the Asian continental plate, which is collectively known as the Sunda Shield, Sunda Plate or Sundaland. Towards the east the islands are much smaller and are called "the Lesser Sunda Islands‟. The transition from oceanic subduction to continent-island arc collision developed in this area, while further west the Banda Arc marks full continent to island arc collision between Australia and the Asian plate. The Australian lithosphere, which is interpreted as Precambrian continental crust is moving northward at a rate that currently varies from 6.7 to 7 cm/year.The Sunda Arc has long been considered as a classical accretionary margin system where the Indo-Australian oceanic plate is underthrust beneath the Asian Continent, active since the Late Oligocene. At the eastern end of the Sunda Arc the convergent system changes from oceanic subduction to continent island arc collision of the Scott Plateau, part of the Australian continent, colliding with the Banda island arc and Sumba Island in between.The Lesser Sunda Islands are also called the inner-arc islands. The formation of these islands is related to the subduction along the Java Trench in the Java Sea. The island of Bali marks the west end of the Lesser Sunda Islands and Alor Island at the east end. To the south of the inner-arc islands, an accretionary wedge formed the outer-arc ridge. The ridge is subaerially exposed in the east as Savu and Timor Island. The northwest of the Lesser Sunda Islands are underlain by a Late Cretaceous Accretionary Crust, which changes to an oceanic crust in the northeast. The Sumba Island has a unique orientation and the origin of the island is still debated.The aim of this article is to provide a broad overview about the structures of the tectonic units based on some selected seismic lines. These lines also give a better geological understanding, including recent processes that developed in the area.